An Experimental Investigation on the Repairing Performance and Fatigue Life of Asphalt Pavement Potholes With an Inclined Interface Joint - Li, Linyu; Huang, Yangquan; Shao, Zhutao; Ren, Dongya (Frontiers in Materials, 2021)
Pothole is a typical structural damage of asphalt pavement, that can significantly influence the life of the asphalt pavement and consequently can driving safety. The durability of the existing pit repair methods is generally lower than that is expected. The existing researches pertinent to pothole repair mainly focused on the selection and amount of tack coat materials, whereas very limited studies addressed the effect of the joint interface shape. Therefore, the aim of this study is to investigate the influence of the interface joint shape on the service life of potholes repair using experimental test. The bond strength and fatigue behavior of the joint were studied and the effectiveness of potholes repair was evaluated under various conditions, including five temperature levels (5oC, 10 oC, 15 oC and 25oC), four strain levels and three loading frequencies (2 Hz, 5 Hz and 10 Hz). The optimal interface joint shape was obtained by orthogonal tests. The results indicated that the bond strength and fatigue life of the high viscoelastic emulsified asphalt with a distribution of 0.6 kg/m2 in the form of 30° inclination joint was 473 and 80 times higher than those of the traditional potholes repair (i.r. vertical joint form, no tack coat), respectively. Finally, a prediction model was proposed for the interface joint fatigue life taking into account external parameters through multiple regression analyses. This prediction model can provide a reference for further asphalt pavement pothole repair study.